Chiral Arylated Amines via C−N Coupling of Chiral Amines with Aryl Bromides Promoted by Light. Issue 39 (20th August 2021) - Song, Geyang; Yang, Liu; Li, Jing‐Sheng; Tang, Wei‐Jun; Zhang, Wei; Cao, Rui; Wang, Chao; Xiao, Jianliang; Xue, Dong
Abstract: The Buchwald‐Hartwig C‐N coupling reaction has found widespread applications in organic synthesis. Over the past two decades or so, many improved catalysts have been introduced, allowing various amines and aryl electrophiles to be readily used nowadays. However, there lacks a protocol that could be used to couple a wide range of chiral amines and aryl halides, without erosion of the enantiomeric excess ( ee ). Reported in this article is a method based on molecular Ni catalysis driven by light, which enables stereoretentive C‐N coupling of optically active amines, amino alcohols, and amino acid esters with aryl bromides, with no need for any external photosensitizer. The method is effective for a wide variety of coupling partners, including those bearing functional groups sensitive to bases and nucleophiles, thus providing a viable alternative to accessing synthetically important chiral N ‐aryl amines, amino alcohols, and amino acids esters. Its viability is demonstrated by 92 examples with up to 99 % ee . Abstract : A stereoretentive C−N coupling of optically active amines and amino acid esters with aryl bromides is achieved by nickel catalysis under light irradiation, without the use of any external photosensitizers.